2005
DOI: 10.1038/sj.cr.7290345
|View full text |Cite
|
Sign up to set email alerts
|

The role of apoptosis in the development and function of T lymphocytes

Abstract: Apoptosis plays an essential role in T cell biology. Thymocytes expressing nonfunctional or autoreactive TCRs are eliminated by apoptosis during development. Apoptosis also leads to the deletion of expanded effector T cells during immune responses. The dysregulation of apoptosis in the immune system results in autoimmunity, tumorogenesis and immunodeficiency. Two major pathways lead to apoptosis: the intrinsic cell death pathway controlled by Bcl-2 family members and the extrinsic cell death pathway controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
112
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(118 citation statements)
references
References 254 publications
(310 reference statements)
2
112
0
4
Order By: Relevance
“…Additionally, we have also demonstrated that the autophagy gene Atg5 contributes critically to the homeostatic survival of mouse T lymphocytes in vivo (35). As this autophagy protein also interacts with FADD (Fas-associated death domain protein) and Bcl-x L (44,45), Atg5 may regulate T cell survival through its role in autophagosome formation or through interactions with extrinsic or intrinsic death pathways (46,47). To determine whether the process of autophagy contributes to mature T cell survival, we examined the T cell compartment in a second autophagy-deficient genetic model system.…”
Section: Survival Defect In Atg7-deficient Mature T Cellsmentioning
confidence: 99%
“…Additionally, we have also demonstrated that the autophagy gene Atg5 contributes critically to the homeostatic survival of mouse T lymphocytes in vivo (35). As this autophagy protein also interacts with FADD (Fas-associated death domain protein) and Bcl-x L (44,45), Atg5 may regulate T cell survival through its role in autophagosome formation or through interactions with extrinsic or intrinsic death pathways (46,47). To determine whether the process of autophagy contributes to mature T cell survival, we examined the T cell compartment in a second autophagy-deficient genetic model system.…”
Section: Survival Defect In Atg7-deficient Mature T Cellsmentioning
confidence: 99%
“…Through this stringent process collectively known as central tolerance, both non-functional T cells and T cells that recognize self-antigens are eliminated. 4 Developing thymocytes depend on glucose for energy production as well as proliferation. 5 Many studies suggest a key role for glucose and glucose metabolism in shaping the thymocyte apoptotic profile.…”
mentioning
confidence: 99%
“…In the immune system, apoptosis is required for lymphocyte development and homeostasis. Dysregulation of apoptosis leads to a variety of immune disorders, including immunodeficiency, tumorogenesis, allergies, and autoimmunity (Zhang et al, 2005). Detection of chemicalinduced thymocyte apoptosis in vivo is difficult, however, because of the rapid clearance of apoptotic cells by phagocytes (Savill and Haslett, 1995;Kamath et al, 1997;Pryputniewicz et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, methoxychlor induced prominent increases in several parameters indicative of induced thymocyte apoptosis, including Annexin V-FITC + cells, caspase (3/7, 8, and 9) activities, and DNA fragmentation. This type of dysregulation of apoptosis in the thymus is known to lead to various immune disorders, including immunodeficiency, tumorigenesis, allergies, and autoimmunity (Zhang et al, 2005). Our previous results demonstrated that short-term exposure has the potential to detect the immunosuppression caused by chemicals present in the environment.…”
Section: Research Articlementioning
confidence: 99%